Translational Pharmacokinetics of Icotrokinra, a Targeted Oral Peptide that Selectively Blocks Interleukin-23 Receptor and Inhibits Signaling - Beverly Knight; Brinda Tammara; Nishit B. Modi; Shannon Dallas; Saro Mardirosian; Jianyao Wang; Aline Laenen; Laurent Leclercq; Karen DiLoreto; Lieve Adriaenssen; Darren Moss; David Polidori; et al. (Dermatology and Therapy)
Abstract Introduction Icotrokinra (formerly JNJ-77242113 or PN-21235) is a targeted oral peptide that selectively inhibits interleukin-23 receptor signaling. The studies described here assessed its absorption, distribution, metabolism, and excretion (ADME), and potential for drug–drug interactions (DDI). Methods In vitro assays evaluated permeability, plasma protein binding, blood-to-plasma partitioning, metabolic stability, and interactions with drug transporters and metabolic enzymes. The nonclinical pharmacokinetic properties of icotrokinra were studied in vivo in rats and monkeys. Phase 1 studies evaluated the pharmacokinetic profile, metabolic profile and excretion in healthy volunteers. Results Icotrokinra demonstrated oral bioavailability of 0.1–0.3% in animals, with evidence of systemic pharmacodynamic activity, without the use of an absorption enhancer. The compound was stable across species in plasma, gastrointestinal matrices, and hepatocytes. Protein binding was low across species (~ 50% in human plasma), and icotrokinra distributed freely to tissues, including skin, joints, and gastrointestinal tissues. Following oral dosing in both rats and monkeys, fecal excretion of unabsorbed drug was the primary elimination route, and metabolite levels were low (each < 2% of dose) in plasma and excreta, with unchanged icotrokinra being the main circulating component. Icotrokinra was neither a substrate nor an inhibitor of prototypical drug transporters or cytochrome P450 enzymes. Icotrokinra exhibited dose-proportional pharmacokinetics from 25 mg to 1000 mg in a first-in-human study, and no serious adverse events were identified following single and multiple dose administrations. Unchanged icotrokinra was the only drug-related component in human plasma. Conclusions Icotrokinra exhibited high stability and an ADME profile consistent with that of a small peptide, with no risk of DDI identified on the basis of in vitro studies. Clinical data demonstrated linear pharmacokinetics and no major metabolites. Trial Registration Number ClinicalTrials.gov, NCT04621630. Euclinicaltrials.eu, EUCT: 2023-504720-26-00. A Graphical Abstract is available for this article. Graphical abstract